Utilisation of telehealth for outpatient diabetes management during COVID‐19 pandemic: how did the patients fare?. Issue 12 (22nd December 2021) - Wong, Vincent W.; Wang, Alexandra; Manoharan, Manimegalai
Abstract: Background: During the Coronavirus disease 2019 (COVID‐19) pandemic, many outpatient services at public hospitals, including diabetes services, had adopted telehealth appointments for their clinic patients. There was concern that patients' glycaemic control may worsen during the pandemic. Aim: To assess glycaemic control of patients with diabetes attending telehealth consultations in 2020, compared to face‐to‐face reviews prior to pandemic. Methods: We conducted a retrospective review of patients with diabetes managed by telehealth consultations over 5 months at two metropolitan hospitals in Sydney. Their attendance rate, glycaemic control and unplanned admissions to hospital were assessed, and these were compared with the same period 12 months prior when patients were reviewed via face‐to‐face appointments. Results: Between April and September 2020, the attendance rate for telehealth consultation at the diabetes services at the two hospitals was 88.9% (884 out of 994), which was higher than in 2019 (85.2%; 818 out of 959; P = 0.016) when patients attended via face‐to‐face appointments. Of the 629 patients reviewed via telehealth in 2020 and who had been with our service for over 12 months, glycaemic control was better in 2020 (HbA1c 7.8 ± 1.4% (62 ± 15 mmol/mol)) compared with 12 months earlier (8.2 ± 1.7% (66 ± 19 mmol/mol); P < 0.001). There was no difference in the number of unplanned admissions for this cohort in 2020 ( n = 58; 9.2%) compared with 2019 ( n = 75; 11.9%; P = 0.100). Conclusions: The present study showed that for patients with diabetes who received care via telehealth consultations during the COVID‐19 lockdown, their glycaemic control was slightly better, and unplanned admission rates were not higher compared with those in the pre‐COVID‐19 period. Telehealth consultation offers an important care delivery option in the management of patients with diabetes under these circumstances.